Boron transfer during desalination by electrodialysis - Han, Le (2020)
Effective boron rejection is challenging, particularly in seawater reverse osmosis (SWRO). Fortunately, electrodialysis (ED) provides a feasible alternative. This study was targeted at a mechanistic understanding of the transfer of boron in ED by systematically evaluating the effects of the chief parameters of solution pH, salinity, boron concentration, current and membrane type. Diffusion and additional transfer are key mechanisms for boron transfer in ED, and the additional transfer is governed by convection for boric acid and migration for borate. Four key results are highlighted. Firstly, boric acid (i.e., at pH = 6.1) transfer was greater than borate (i.e., at pH = 10.8) transfer, giving the permeability and additional transfer coefficient of the former of respectively an order-of-magnitude and twofold that of the latter. Secondly, while changes in salt concentrations had negligible impact on boric acid flux, borate flux decreased with NaCl concentration due to increased competition with the chloride ions. Thirdly, boron permeability was greater for the RO membranes than the ion-exchange membranes (IEMs) due to different membrane properties, and boron permeability decreased with pH for both the RO membranes and IEMs due respectively to electrostatic repulsion and competition for charge carriers. Fourthly, the percentage of boric acid transferred decreased with current, which suggests enhanced boron rejection as current increased. Collectively, results indicate that ED is promising for boron removal, and is possibly more effective than RO in boron rejection both because of the different membrane properties and transfer mechanisms.